2015
DOI: 10.1080/15685551.2015.1092015
|View full text |Cite
|
Sign up to set email alerts
|

Monomers for adhesive polymers, 17.aSynthesis, photopolymerization and adhesive properties of polymerizable phosphonic acids bearing urea groups

Abstract: Four polymerizable phosphonic acids bearing urea groups 4a, 4b, 9a, and 9b as well as the 10-(methacryloyloxy)decylphosphonic acid 10 were synthesized in four to six steps. They were characterized by 1 H, 13 C, and 31 P NMR spectroscopy and by high-resolution mass spectroscopy. Contrary to methacrylates 4a and 4b, methacrylamides 9a and 9b were hydrolytically stable in deuterated water/deuterated ethanol solutions. The photopolymerization behavior of acidic monomers 4a, 4b, 9a, 9b, and 10 and their correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…They were found to be more reactive than TEGDMA due to a combination of hydrogen abstraction/chain transfer reactions via the labile hydrogens and hydrogen bonding caused by the urea linkage. Moszner et al described the synthesis of polymerizable phosphonic acids bearing urea groups and showed that the presence of urea group led to a significant increase in both rate of polymerization and shear bond strength to dental tissues …”
Section: Introductionmentioning
confidence: 99%
“…They were found to be more reactive than TEGDMA due to a combination of hydrogen abstraction/chain transfer reactions via the labile hydrogens and hydrogen bonding caused by the urea linkage. Moszner et al described the synthesis of polymerizable phosphonic acids bearing urea groups and showed that the presence of urea group led to a significant increase in both rate of polymerization and shear bond strength to dental tissues …”
Section: Introductionmentioning
confidence: 99%
“…These monofunctional methacrylates with enhanced rates and conversions were found to have potential to be used as diluent monomers in dental formulations. Then, phosphonic acids bearing urea groups were synthesized to improve the performance of self‐etching adhesives by Moszner and coworkers and the presence of a urea group was shown to significantly increase both the rate of polymerization and the shear bond strength to both dentin and enamel …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, acidic monomers exhibiting strong chelating properties were synthesized and tested in SEAs. It has been demonstrated that the adhesion of SEAs can be improved when polymerizable diphosphonic acids,[ 10–12 ] β-ketophosphonic acids [ 13 ] or phosphonic acids bearing urea groups [ 14 ] are used as acidic monomer. Gem-phosphonate-phosphates were found to be potential antiatherosclerotic agents.…”
Section: Introductionmentioning
confidence: 99%